2010
DOI: 10.1021/jo102051z
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and Iodine Atom-Economic Co-Iodination of Alkenes

Abstract: Molecular iodine, I(2), is readily converted into 2 equiv of acetyl hypoiodite (CH(3)CO(2)I) via oxidation by (diacetoxyiodo)benzene (DAIB) followed by trapping of the iodide ion by acetoxyphenyl iodonium ion formed. The in situ generated CH(3)CO(2)I is utilized for the synthesis of 1,2-iodo-cofunctionalized derivatives of a variety of alkenes. Conversion of both iodine atoms of I(2) to I(+) sources results in 100% iodine atom economy for the reported iodo-cofunctionalization of alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…[37,38] To the best of our knowledge, this is the first report on the opening of the thiiranium ring with an alkene. As in the case of the first route, the carbocation intermediate then reacts with another molecule of the styrene component to give benzylic carbocation III.…”
Section: Entry Styrenementioning
confidence: 86%
See 2 more Smart Citations
“…[37,38] To the best of our knowledge, this is the first report on the opening of the thiiranium ring with an alkene. As in the case of the first route, the carbocation intermediate then reacts with another molecule of the styrene component to give benzylic carbocation III.…”
Section: Entry Styrenementioning
confidence: 86%
“…[37,38] This intermediate then reacts with the styrene to Scheme 3. The reaction commences with the formation of the hypervalent intermediate II.…”
Section: Entry Styrenementioning
confidence: 99%
See 1 more Smart Citation
“…36 Similarly, the vinyl group at the C3-position of 1 can also be converted into the C3-[(1-hydroxy-2-iodo)ethyl], C3-[(1-methoxy-2-iodo)ethyl] and C3-[(1-ethoxy-2-iodo)ethyl] groups by the I 2 -PIFA system (Scheme 1). 35 Compound 1 was mixed with I 2 (1.2 equiv) and PIFA (0.52 equiv) in 1,2-dichloroethane, followed by stirring at room temperature for 1 h. Then ethylene glycol was added to this solution, and an additional stirring afforded an ethylene glycol adduct 2, possessing a [1-(2-hydroxyethyloxy)-2-iodo]ethyl moiety at the C3-position, in 50% isolated yield.…”
mentioning
confidence: 99%
“…Unfortunately, none afforded any evidence of cyclized material irrespective of the rate and/or order of addition. However, we found that if electrophilic iodine in the form of iodine/hypoiodide was generated in situ either by reacting PhI(OAc) 2 with I 2 or under heterogeneous conditions with Oxone® and KI, [12] the desired [3.2.2]-bicyclic system of 16 could be formed in modest amounts (~20% in the latter case) alongside several uncharacterized side-products suggestive of over- and/or non-selective halogenation. While this finding was encouraging, a superior material throughput was needed for effective prosecution of the sequence.…”
mentioning
confidence: 99%